Aspectos ecológicos de insetos predadores e fitófagos associados à nogueira-macadâmia em Jaboticabal, São Paulo - Matos, Sidnéia Terezinha Soares de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
A nogueira-macadâmia (Macadamia integrifolia Maiden e Betche), originária da Austrália, encontra-se em expansão no Brasil. Por ser uma cultura recentemente introduzida no País, a maioria das informações e as tecnologias recomendadas para sua produção foram adaptadas de pesquisas efetuadas para as condições edafoclimáticas dos Estados Unidos e da Austrália. Esse fato ressalta a necessidade de se desenvolver estudos sobre a fauna entomológica, visando ao manejo integrado de pragas dessa nogueira. No presente estudo, foi realizado levantamento populacional de insetos em nogueira-macadâmia em Jaboticabal, São Paulo. O objetivo foi identificar as principais espécies de insetos fitófagos e predadores e determinar as espécies predominantes por meio de estudos de flutuação populacional desses organismos em relação aos estádios fenológicos da cultura. O total de 540 exemplares de insetos predadores foram coletados pertencentes a 8 ordens, 13 famílias e 37 espécies; os insetos fitófagos totalizaram 7588 exemplares de 5 ordens, 35 famílias e 83 espécies. Os predadores Chrysoperla externa (Hagen) (Neuropetra: Chrysopidae), Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), Allograpta hastata Fluke (Diptera: Syrphidae) e Nusalala sp. (Neuroptera: Hemerobiidae) e os fitófagos Toxoptera aurantii (Fonscolombe) Hemiptera: Aphididae), Frankliniella gardeniae Moulton (Tysanoptera: Thripidae), Haplothrips gowdeyi (Franklin) (Tysanoptera: Phlaeothripidae), Mormidea sp., Piezodorus sp. (Hemiptera: Pentatomidae), Zicca sp. (Hemiptera: Coreidae), Stenocoris sp. (Hemiptera: Alydidae), Diabrotica speciosa (Germar) (Coleoptera: Chrysomelidae), Charidotis marginella (Fabricius) (Coleoptera: Chrysomelidae), Ophiderma sp. (Hemiptera: Membracidae), Epitragus sp.3 (Coleoptera Tenebrionidae) e Ptilodactyla sp.2 (Coleoptera: Ptilodactylidae) classificaram-se como predominantes. Os maiores índices de diversidade e picos populacionais das espécies predominantes ocorreram no estádio de floração.

The macadamia nut (Macadamia integrifolia Maiden e Betche) is native from Australia and is in expansion in Brazil. It was recently introduced in the country, therefore, most of the knowledges and technologies recommended for production were adapted from researches conducted for soil and climatic conditions in United States and Australia. This fact highlights the importance of studies about the entomological fauna, aiming at the integrated pest management of this walnut. In this study was conducted a population survey of insects in macadamia nut in Jaboticabal, São Paulo. The objective was to identify the main species of phytophagous insects and predators and to determine the predominant species through the study of its population dynamics in relation to the phenological stages of the crop. A total of 540 predatory insects specimens belonging to eigth orders, 13 families and summing up 37 species were collected. A total of 7588 specimens of phytophagous insects from five orders, 35 families and and summing up 83 species were captured. The insect predators Chrysoperla externa (Hagen) (Neuropetra: Chrysopidae), Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), Allograpta hastata Fluke (Diptera: Syrphidae) e Nusalala sp. (Neuroptera: Hemerobiidae) and the insect phytophagous Toxoptera aurantii (Fonscolombe) Hemiptera: Aphididae), Frankliniella gardeniae Moulton (Tysanoptera: Thripidae), Haplothrips gowdeyi (Franklin) (Tysanoptera: Phlaeothripidae), Mormidea sp., Piezodorus sp. (Hemiptera: Pentatomidae), Zicca sp. (Hemiptera: Coreidae), Stenocoris sp. (Hemiptera: Alydidae), Diabrotica speciosa (Germar) (Coleoptera: Chrysomelidae), Charidotis marginella (Fabricius) (Coleoptera: Chrysomelidae), Ophiderma sp. (Hemiptera: Membracidae), Epitragus sp.3 (Coleoptera Tenebrionidae) e Ptilodactyla sp.2 (Coleoptera: Ptilodactylidae) were classified as predominant. The highest species diversity and population peak of predominant species occurred during the flowering stage.
Ecological aspects of predators and phytophagous insects associated to nogueira-macadamia in Jaboticabal, São Paulo
Keywords: Diversidade; Flutuação populacional; Inimigos naturais; Pragas; Population fluctuation; Natural enemies; Pests; Macadamia integrifolia; Diversity